A patient‐centred approach to determine optimal supportive care across the cancer trajectory: a cross‐sectional study. (21st April 2021) - Turon, Heidi; Hill, David; Watson, Rochelle; Hobden, Breanne; Millar, Jeremy; Sanson‐Fisher, Rob
Abstract: Objective: Supportive care is recognised as an integral component of cancer care. To comprehensively improve supportive care and to inform policy, it is essential to examine consumer's views of health services. This study aimed to develop and test a patient‐centred approach by measuring consumer perspectives on the importance of aspects of supportive care to determine what patients consider highest quality or 'optimal' care. Methods: A cross‐sectional survey was conducted in oncology outpatient clinics. Eligible patients were invited to complete the optimal care survey on an iPad. The survey consisted of 69 items assessing 14 care domains across five phases of the care trajectory. Results: A total of 359 participants completed the survey. Items in the 'preparation for treatment' and 'follow‐up and end‐of‐life care' phases were endorsed as very important/essential to optimal care by most participants (79–97% and 80–100%, respectively). Items in the 'preparation for first appointment' (48–84%), 'first appointment' (51–97%) and 'receiving treatment' (32–93%) phases showed greater variation in endorsement. Conclusion: This study provides a patient‐centred tool for quantifying optimal supportive care for people with cancer across the treatment trajectory. This tool could be used by healthcare providers to evaluate existing care quality, develop policies and guide clinical service improvements.